ANALYSIS OF SERVICE QUALITY AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN BOGOR REGENCY - Syahrir (PT. Sangadji Media Publishing, 2023)
This study aims to investigate the quality of public services at the Population and Civil Registry Office of Bogor Regency. The research method used was quantitative with a descriptive statistical approach, involving 95 respondents selected through total sampling. The findings from the descriptive statistical test show that the quality of public services at the Bogor District Population and Civil Registration Office is generally considered